Effects of chronic antipsychotic drug exposure on the expression of Translocator Protein and inflammatory markers in rat adipose tissue. (September 2018) - Calevro, Anita; Cotel, Marie-Caroline; Natesan, Sridhar; Modo, Michel; Vernon, Anthony C.; Mondelli, Valeria
Highlights: Olanzapine increases IL-6 and macrophage expression in rat adipose tissue. Antipsychotic treatment does not change expression of TSPO in rat adipose tissue. Adipose TSPO increases when macrophage expression increases, following olanzapine. Abstract: The precise effect of antipsychotic drugs on either central or peripheral inflammation remains unclear. An important issue in this debate is to what extent the known peripheral metabolic effects of antipsychotics, including increased adiposity, may contribute to increased inflammation. Adipose tissue is known to contribute to the development of systemic inflammation, which can eventually lead to insulin resistance and metabolic dysregulation. As a first step to address this question, we evaluated whether chronic exposure to clinically comparable doses of haloperidol or olanzapine resulted in the immune activation of rat adipose tissue. Samples of visceral adipose tissue were sampled from male Sprague–Dawley rats exposed to, haloperidol, olanzapine or vehicle (all n = 8), for 8 weeks. From these we measured a cytokine profile, protein expression of F4/80 (a phenotypic macrophage marker) and translocator protein (TSPO), a target for radiotracers putatively indicating microgliosis in clinical neuroimaging studies. Chronic olanzapine exposure resulted in significantly higher adipose IL-6 levels compared with vehicle-controls (ANOVA p = 0.008, Bonferroni post-hoc test p = 0.006); in parallel, animals exposed to olanzapine had significantly higher F4/80 expression when compared with vehicle-controls (Mann Whitney Test, p = 0.014), whereas there was no difference between haloperidol and vehicle groups (Mann Whitney test, p = 0.1). There were no significant effects of either drug on adipose TSPO protein levels. Nevertheless, we found a positive correlation between F4/80 and TSPO adipose protein levels in the olanzapine-exposed rats (Spearman's rho = 0.76, p = 0.037). Our data suggest that chronic exposure to olanzapine, but not haloperidol, increases production of the pro-inflammatory cytokine IL-6 in adipose tissue and increased macrophages expression (F4/80), in the absence of measurable changes in TSPO with respect to vehicle. This may have potentially important consequences in terms of metabolic dysregulation associated with long-term antipsychotic treatment.